Thyroid dysfunction in a patient with aglossia - Kantaputra P. (2014)
We report a Thai girl who had aglossia, micrognathia, microsomia, collapse of mandibular arch, persistence of buccopharyngeal membrane, microcephaly, and mild developmental delay. Thyroid function tests indicated that she had subclinical hypothyroidism. Thyroid scan revealed normal uptake of the whole thyroid gland. Tongue morphogenesis is integrally linked to the normal development of thyroid gland, and abnormal tongue morphogenesis could potentially result in a functional thyroid disorder. We propose that micrognathia, microsomia, congenital absence of mandibular incisors, and collapse of the mandibular arch are the result of abnormal tongue development. © 2003 Wiley-Liss, Inc.